THE IMPACT OF INTERNAL DISPLACE PERSON AND REFUGEES IMMIGRANT IN SOUTH SUDAN - Alier, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Internal Displace Persons and Refuges Refugees move out of fear or necessity. e.g. to flee persecution; or because their homes were destroyed in a natural disaster; or due to war, violence, political opinion, human rights violations; or due to their religion, beliefs or political opinionAn Immigrant is an individual who leaves one’s country to settle in another, whereas refugees are defined as persons, who move out of one’s country due to restriction or danger to their lives. Immigration is considered a natural phenomenon in population ecology, whereas the refugee movement occurs only under some kind of coercion or pressure.Refugees, on the other hand, move out due to fear of persecution caused by war, violence, political instability, aggression or due to their religion, beliefs, caste, or political opinion. In most cases, it is not possible for them to go back to their country.